2020
DOI: 10.18805/ijar.b-3874
|View full text |Cite
|
Sign up to set email alerts
|

Induced Breeding and Developmental Biology of Endemic Western Ghats Fish Dawkinsia filamentosa (Valenciennes, 1844) under Captive Conditions

Abstract: In the present study, induced breeding of endemic barb, Dawkinsia filamentosa was carried out using three different synthetic hormones namely Human chorionic gonadotropin (HCG), WOVA-FH and Ovatide at different (0.3, 0.5, 0.7 and 0.9 ml/Kg) doses. All synthetic hormones showed good performance at 0.7 ml/kg body weight. Comparatively WOVA-FH showed better performance with higher number of spawned eggs (1405±5.74 nos/female) and hatching rate (90±0.6%). The study concluded that WOVA-FH at 0.7 ml/kg is an ideal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 8 publications
3
13
0
Order By: Relevance
“…Hatching was observed 33-35 h after the fertilization, and WOVA-FH and percentage of fertilization and hatching rate were also greatly affected by the dose of hormone used. Rath et al (2007) et al, 1992;Islam & Chowdhury, 1976;Mahadevi et al, 2020aMahadevi et al, , 2020bSiddik et al, 2013). Egg and embryonic development was more similar to the cyprinid fish, and similar observations were reported by Mahadevi et al (2020a) and (2020b) for D. filamentosa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hatching was observed 33-35 h after the fertilization, and WOVA-FH and percentage of fertilization and hatching rate were also greatly affected by the dose of hormone used. Rath et al (2007) et al, 1992;Islam & Chowdhury, 1976;Mahadevi et al, 2020aMahadevi et al, , 2020bSiddik et al, 2013). Egg and embryonic development was more similar to the cyprinid fish, and similar observations were reported by Mahadevi et al (2020a) and (2020b) for D. filamentosa.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous trials conducted on breeding of the other species of same genus such as D . filamentosa (Mahadevi et al, ,2020a, 2020b), WOVA‐FH hormone has shown promising results; hence, this hormone was selected to induce breed D . rohani .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations